0155 SUVN-G3031, A Potent and Selective Histamine H3 Receptor Inverse Agonist - Differentiating Features Over Current Treatments of Narcolepsy. (27th May 2020) - Shinde, A; Subramanian, R; Palacharla, R; Pandey, S; Benade, V; Jayarajan, P; Bojja, K; Nirogi, R
Abstract: Introduction: Majority of pharmacological agents used in the treatment of narcolepsy have several limitations. Both nonclinical and clinical evidences suggest usefulness of the histamine H3 receptor (H3R) inverse agonists for the treatment of narcolepsy and addressing several of the current limitations. Methods: Extensive nonclinical studies were carried out for SUVN-G3031 and other pharmacological agents that are currently being used for the treatment of narcolepsy. Nonclinical parameters like inter-species binding affinity, selectivity profile, in vivo and in vitro ADME features, nonclinical efficacy, neurochemistry and safety were compared. Results: SUVN-G3031 has no inter-species variation in binding affinity at H3R with less than 50% inhibition at 1 µM against 70 other targets. Unlike pitolisant, SUVN-G3031 has no significant binding affinity at sigma 1 and 2 receptor. SUVN-G3031 has no inhibition and induction liability towards major CYP enzymes and transporters. Pitolisant is reported to be a CYP3A4, CYP2B6, and CYP1A2 inducer and a CYP2D6 and OCT1 inhibitor. SUVN-G3031 has robust wake promoting effects. SUVN-G3031 showed negligible affinity towards hERG channel with IC50 > 10 µM and had no effects on any ECG parameters in dog telemetry study. SUVN-G3031 did not show convulsion in rats up to the tested dose of 100 mg/kg, p.o. Most of the pharmacological agents used for the treatment of narcolepsy have abuse liability; SUVN-G3031 produced no change in the striatal and accumbal dopamine levels in rats suggesting no propensity to induce abuse liability. Unlike competing H3R inverse agonists, SUVN-G3031 has no effects on fertility and embryo-fetal development up to the highest tested doses. Conclusion: Nonclinical studies demonstrate superiority of SUVN-G3031 over pharmacological agents currently used in the treatment of narcolepsy. SUVN-G3031 is being evaluated in a Phase 2 study as monotherapy for the treatment of narcolepsy with and without cataplexy (ClinicalTrials.gov Identifier: NCT04072380). Support: None